STATUS KUALITAS SUNGAI MUSI BAGIAN HILIR DITINJAU DARI KOMUNITAS FITOPLANKTON - Hilda Zulkifli; Husnah; Moh. Rasyid Ridho; Suhodo Juanda (The East Java Biological Society, 2009)
Musi river is the main source of water for society and industry on the downstream area, and also becomes the waste disposal area for domestic/industry. The objective of this study was to evaluate the status of Musi river on the downstream area based on phytoplankton community (from the Pulokerto district to downstream of musi river on Tanjung Buyut Village). The sample of water surface and plankton were taken compositely on 18 stations. The water quality analysis is held on LIPI Bogor, while the identification of microscopic community of phytoplankton is held on BRPPU Mariana. The result of research showed that phytoplankton community on observed locations comprises of Chlorophyta with 18 genus (45.34%), followed by Cyanophyta with 7 genus (26.09%), Baccillariophyta with 14 genus (25.81%) and Euglenophyta with 2 genus (2.17%). The Oscillatoria (Cyanophyta) is found on most of observed locations. Based on the examination of saprobic status, Pulokerto station is categorized as “moderate polluted” or (ά/ß –mesosaprobik dan ß/ά –mesosaprobik), while closer to downstream of Musi river is categorized as “low polluted” or (oligo/ß –mesosaprobic).